Realising 'will, preferences and rights': reconciling differences on best practice support for decision-making?. Issue 4 (2nd October 2019) - Carney, Terry; Then, Shih-Ning; Bigby, Christine; Wiesel, Ilan; Douglas, Jacinta; Smith, Elizabeth
ABSTRACT: 'Will, preferences and rights' is the new guiding principle for all support for or exercise of decision-making under the Convention on Rights of Persons with Disabilities, but its meaning is disputed and practice implications are poorly understood. This article explores key debates across disciplines and draws on grounded theory fieldwork findings to bring greater clarity to the principle within law, policy and practice settings. It is argued that the principle calls for a nuanced understanding which cautions against expectations that mere enactment into law or adoption within programs of support will prove to be a panacea.